Pengembangan Media Pembelajaran Mandiri Berbasis Digital untuk Meningkatkan Literasi Membaca di Sekolah Dasar - Takwin, Ira; Rosdiana, Rosdiana; Mirnawati, Mirnawati (Socratika: Journal of Progressive Education and Social Inquiry, 2024)
This study aims: (1) To determine the needs analysis of digital literacy-based learning media in grade V SDN 34 Bara Palopo City. (2) To describe the process of developing digital-based learning media for reading comprehension learning on theme 6 in grade V SDN 34 Bara Palopo City. (3) To determine the feasibility and practicality of digital-based learning media for reading comprehension learning on theme 6 in grade V SDN 34 Bara Palopo City. The research conducted was of the R&D (Research and Development) type with the 4D development model (define, design, develop, and disseminate). The data collection techniques used were observation, interviews, and questionnaires to educators and students. The data obtained were then analyzed qualitatively and quantitatively. This research produces digital literacy-based learning media in the form of digital storybooks and can be accessed using smartphones and laptops / PCs. validated by 3 experts, namely linguists with a value of 91% (very valid category), material experts with a value of 92% (very valid category), and media experts with a value of 86% (very valid category).For the practicality test, the results obtained from students were 84.43% and from educators were 100%, both of which met the very practical category. This shows that the product developed has a high level of validity, so the product developed by the researcher is suitable for learning activities at school. Researchers hope that the products developed can be used as alternative media used by teachers and students with the help of smartphones and laptops / PCs related to reading comprehension learning.